Photodynamic therapy by conjugation of cell-penetrating peptide with fluorochrome - Park CK (Dove Medical Press, 2017)
Chul-Kyu Park,1,* Yong Ho Kim,1,* Suhyun Hwangbo,2 Hoonsung Cho2 1Department of Physiology, College of Medicine, Gachon University, Incheon, 2School of Materials Science & Engineering, Chonnam National University, Gwangju, South Korea *These authors contributed equally to this work Abstract: Photodynamic therapy (PDT) is a promising alternative therapy that could be used as an adjunct to chemotherapy and surgery for cancer, and works by destroying tissue with visible light in the presence of a photosensitizer (PS) and oxygen. The PS should restrict tissue destruction only to the tumor and be activated by light of a specific wavelength; both of these properties are required. Arginine-rich peptides, such as cell-penetrating peptides, have membrane-translocating and nuclear-localizing activities, which have led to their application in various drug delivery modalities. Protamine (Pro) is an arginine-rich peptide with membrane-translocating and nuclear-localizing properties. The reaction of an N-hydroxysuccinimide (NHS) ester of rhodamine (Rho) and clinical Pro was carried out in this study to yield RhoPro, and a demonstration of its phototoxicity, wherein clinical Pro improved the effect of PDT, was performed. The reaction between Pro and the NHS ester of Rho is a solution-phase reaction that results in the complete modification of the Pro peptides, which feature a single reactive amine at the N-terminal proline and a single carboxyl group at the C-terminal arginine. This study aimed to identify a new type of PS for PDT by in vitro and in vivo experiments and to assess the antitumor effects of PDT, using the Pro-conjugated PS, on a cancer cell line. Photodynamic cell death studies showed that the RhoPro produced has more efficient photodynamic activities than Rho alone, causing rapid light-induced cell death. The attachment of clinical Pro to Rho, yielding RhoPro, confers the membrane-internalizing activity of its arginine-rich content on the fluorochrome Rho and can induce rapid photodynamic cell death, presumably owing to light-induced cell membrane rupture. PDT using RhoPro for HT-29 cells was very effective and these findings suggest that RhoPro is a suitable candidate as a PS for solid tumors. Keywords: photodynamic therapy, rhodamine, protamine, endocytosis, cell-penetrating peptide